2014
DOI: 10.1037/a0037500
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the Psychopathy Checklist: Youth Version (PCL:YV) among male adolescent offenders: An item response theory analysis.

Abstract: This study examined the applicability of the Psychopathy Checklist: Youth Version (PCL:YV; Forth, Kosson, & Hare, 2003) among a large sample of serious offending adolescent males. Adopting an item response theory approach, item properties of the PCL:YV were examined using the generalized partial credit model. Results showed that need for stimulation, "irresponsibility," and callous & unemotional were sensitive to changes in respondents' varying psychopathy levels, whereas lack of realistic, long-term goals; su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 54 publications
2
17
2
Order By: Relevance
“…Some of the items in this study with higher discrimination parameters also presented good parameters in the study by Tsang et al (2014), such as "Callous/Lack of Empathy" and "Lack of Remorse/ Guilt", suggesting that these attributes are good indicators for differentiating between different levels of psychopathy traits. Similarly, items such as "Need for Stimulation" also proved to be poorly discriminating in other studies (Tsang et al, 2015(Tsang et al, , 2014, suggesting that this is a more universal feature of adolescence and therefore less informative for the purpose of the PCL: YV. Other items also presented more inconsistent discriminations in these multiple studies, such as, for example, the item "Shallow emotions".…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Some of the items in this study with higher discrimination parameters also presented good parameters in the study by Tsang et al (2014), such as "Callous/Lack of Empathy" and "Lack of Remorse/ Guilt", suggesting that these attributes are good indicators for differentiating between different levels of psychopathy traits. Similarly, items such as "Need for Stimulation" also proved to be poorly discriminating in other studies (Tsang et al, 2015(Tsang et al, , 2014, suggesting that this is a more universal feature of adolescence and therefore less informative for the purpose of the PCL: YV. Other items also presented more inconsistent discriminations in these multiple studies, such as, for example, the item "Shallow emotions".…”
Section: Discussionsupporting
confidence: 51%
“…Choosing not to consider the hypothesis of items with the same discrimination (the case of Rasch models), one has to choose between two polytomic models: the Generalized Partial Credit Model (GPCM) (Masters, 1982;Muraki, 1992) or the Graded Response Model (GRM) (Samejima, 1968). According to Tsang, Piquero, and Cauffman (2014), although appropriate for categorical responses, GRM assumes that the likelihood of responding to a higher category increases as the latent trait increases.…”
Section: Model Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two factor scores assessing interpersonal/affective features (F1: sum of eight items) and social deviance characteristics (F2: sum of nine items) are also available. Excellent inter-rater reliability (ICC = .91) was reported during training on the PCL:YV (Tsang, Piquero, & Cauffman, 2014). …”
Section: Methodsmentioning
confidence: 92%
“…In particular, research comparing African American and Caucasian samples has shown modest to substantial differences in item slope and threshold estimates (Cooke & Michie, 2001;Tsang, Piquero, & Cauffman, 2014) and differences in underlying factor structures of psychopathy have been reported as well (Kosson, Smith, & Newman, 1990;Sullivan & Kosson, 2006). For example, Tsang et al (2014) found differential item functioning of estimated thresholds in 10 of the 20 PCL:YV items among Caucasian and African American boys, and further noted four items that were more sensitive to change (i.e., had larger estimated slopes) for Caucasian compared to African American participants. In addition, it is important to point out that the overwhelming majority of this work has focused on adult correctional and forensic psychiatric samples, using PCL based measures.…”
Section: Invariance Across Racementioning
confidence: 99%